What is new in the research on cadmium-induced stress in plants? - Azevedo, Ricardo A.; Gratao, Priscila L. [UNESP]; Monteiro, Carolina C. [UNESP]; Carvalho, Rogerio F. [UNESP] (Wiley-Blackwell, 2012)
Cadmium (Cd) is an important metal due to its industrial use but also one of the most dangerous metals because of its accumulation in the environment. This can eventually lead to entrance into the food chain if the Cd is taken up by crop plants used for feeding animals and humans. Thus, a large number of reviews have discussed the many aspects of stress induced by Cd and other metals in a wide range of species. In relation to plants, useful reviews have been published over the years regarding molecular and biochemical aspects of Cd stress. In this minireview, we have concentrated on promising and emerging topics of Cd-stress research in plants, such as hormonal control of the antioxidant system and interaction between organisms and plants.
Keywords: Antioxidant system; cadmium stress; hormones; phytoremediation; plant stress